Objectification of Women in Waifu Depictions: An Analysis from the Male Gaze Perspective - Saraswati, Lidya; Paramita, Ni Made Savitri; Ambarastuti, Retno Dewi (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Popular culture is a form of culture that various groups can easily enjoy. The spread of a culture from one region to another is also influenced by globalization. One example of this is the introduction of Japanese culture into Indonesia, which has familiarized Indonesian society with Japanese popular culture, such as anime. Anime enthusiasts, known as otaku, often develop an interest in fictional female characters in anime, commonly referred to as waifu. This study employs Laura Mulvey's theory of the male gaze, Martha Nussbaum's theory of objectification, and Jean Baudrillard's concept of hyperreality. The research utilizes qualitative methods, including distributing questionnaires to all members of the Otaku Sidoarjo community and conducting interviews with five members who are interested in anime, to examine the depiction and attraction that anime otaku have towards fictional female characters in anime. The findings indicate that the objectification of women occurs in the depiction of waifu according to anime otaku, relating to the male gaze perspective and hyperreality. This is evidenced by respondents having specific criteria for viewing the fictional female characters they favor. This phenomenon is also connected to hyperreality, as respondents are caught in a false reality created by their attraction to fictional female characters designated as waifu.